2011
DOI: 10.4067/s0716-97602011000200008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypoxia on epididymal sperm parameters and protective role of ibuprofen and melatonin

Abstract: Hypobaric hypoxia is of interest due to an increase of human populations working at high altitude. Testicular damage is related to the physiological response (neoangiogenesis) to increased intrascrotal blood fl ow as temperature rises. Hypoxia is a stress factor with overproduction of reactive oxygen species (ROS). The effect of hypoxia in mice reproductive parameters is analyzed. Animals were exposed to simulated hypoxia of 4,200 meters above sea level (m.a.s.l.) in a chamber for 33.2 days, both to continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 49 publications
1
32
2
3
Order By: Relevance
“…The present study demonstrated that intermittent hypobaric hypoxia induces lipid peroxidation in testis and epididymis, as previously reported (Farias et al, 2010;Vargas et al, 2011). However, in the aforementioned studies melatonin did not have any effect with the doses used in contrary to other reports where melatonin had a protective role in testis and spermatogenesis of rats subjected to intermittent hypobaric hypoxia (Hartley et al, 2009;Bustos-Obregón et al, 2010;Vargas et al, 2011);Ahmad & Haldar (2010) as well as hamsters and rats, where melatonin seems to act directly on Leydig cells to suppress testosterone release in vitro.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The present study demonstrated that intermittent hypobaric hypoxia induces lipid peroxidation in testis and epididymis, as previously reported (Farias et al, 2010;Vargas et al, 2011). However, in the aforementioned studies melatonin did not have any effect with the doses used in contrary to other reports where melatonin had a protective role in testis and spermatogenesis of rats subjected to intermittent hypobaric hypoxia (Hartley et al, 2009;Bustos-Obregón et al, 2010;Vargas et al, 2011);Ahmad & Haldar (2010) as well as hamsters and rats, where melatonin seems to act directly on Leydig cells to suppress testosterone release in vitro.…”
Section: Discussionsupporting
confidence: 75%
“…However, in the aforementioned studies melatonin did not have any effect with the doses used in contrary to other reports where melatonin had a protective role in testis and spermatogenesis of rats subjected to intermittent hypobaric hypoxia (Hartley et al, 2009;Bustos-Obregón et al, 2010;Vargas et al, 2011);Ahmad & Haldar (2010) as well as hamsters and rats, where melatonin seems to act directly on Leydig cells to suppress testosterone release in vitro. When administered orally at 10 mg/kg bodyweight, melatonin has been described as a counteracting substance for testis and spermatogenesis damage in rats subjected to intermittent hypobaric hypoxia (Vargas et al, 2011). The present results showed that melatonin, with the doses given via intraperitoneal, had no protective effect in testis and epididymis.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Como también la evaluación del rol protector de distintas sustancias, tanto químicas como naturales sobre la función reproductiva de los organismos expuestos a los contaminantes descritos anteriormente. (Contreras et al, 1996., Bustos-Obregón et al, 1998., ., , 2010, 2013., Vargas et al, 2011, Bustos Obregón & Olivares 2012., Valenzuela et al, 2014.…”
Section: Logros Del Prof Doctor Bustos-obregónunclassified
“…Greater testicular damage have been observed under continuous hypoxia. With intermittent hypoxia, lesions are less essential, suggesting that cycles of normoxia compensate the effects on the testicle (Vargas et al, 2011).…”
Section: Introductionmentioning
confidence: 99%